USABILITY EVALUATION OF ONLINE LOANING APPLICATION FOR âCICILâ STUDENTS - Emanuela, Ellen
The rapid development of information technology has changed various sector of our life, including Economy. Cicil, as one of the startup companies in Indonesia, utilizes technology to deliver its services to its customer. Cicil is a financial technology lending company that tries to answer the needs of university students in Indonesia for an alternative source of funding. Users could access lending services through Cicil website and mobile application. According to the initial study, users still find it difficult to use Cicil mobile application resulting in low user satisfaction. The purpose of this study is to increase Cicil mobile application’s usability by conducting usability evaluation for several features including, creating a new account, completing profile registration, applying for university tuition lending, and applying for goods lending. Usability evaluation was held by conducting usability testing using the parameter effectivity, efficiency, and satisfaction. This study utilizes remote usability testing and involved 20 participants. Based on the result, Cicil mobile application is not optimized in terms of effectiveness, efficiency, and satisfaction. Using the System Usability Scale, overall user satisfaction was measured, and it was discovered that Cicil Mobile application is in 15-34 percentile (grade D). Using the Concept Generation Method, 21 recommendations were proposed to increase the usability of Cicil mobile application.